Proceedings of the Twenty-Ninth Annual ACM-SIAM Symposium on Discrete Algorithms 2018
DOI: 10.1137/1.9781611975031.130
|View full text |Cite
|
Sign up to set email alerts
|

Testing Ising Models

Abstract: Given samples from an unknown multivariate distribution p, is it possible to distinguish whether p is the product of its marginals versus p being far from every product distribution? Similarly, is it possible to distinguish whether p equals a given distribution q versus p and q being far from each other? These problems of testing independence and goodness-of-fit have received enormous attention in statistics, information theory, and theoretical computer science, with sample-optimal algorithms known in several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…In the case of logistic regression, there has been a lot of work showing that under certain hightemperature conditions on the Ising model (which are similar to the assumptions we make in our paper), one can perform many statistical tasks such as learning, testing and sampling of Ising models efficiently [28,14,13,15,25,17].…”
Section: Modeling Dependencementioning
confidence: 71%
“…In the case of logistic regression, there has been a lot of work showing that under certain hightemperature conditions on the Ising model (which are similar to the assumptions we make in our paper), one can perform many statistical tasks such as learning, testing and sampling of Ising models efficiently [28,14,13,15,25,17].…”
Section: Modeling Dependencementioning
confidence: 71%
“…Since lower bounds of [ADK15] show that distribution testing suffers from the curse of dimensionality, further structural assumptions must be made if one wishes to test multivariate distributions. This "highdimensional frontier" has also been studied on graphical models by [DDK18] and [CDKS17] (for Ising models and Bayesian networks, respectively).…”
Section: Related Workmentioning
confidence: 99%
“…The detection problem we consider is in part inspired by the works Addario-Berry et al (2010); Arias-Castro et al (2012, 2015b Berthet et al (2016); Mukherjee et al (2016). An interesting paper on testing goodness-of-fit in Ising models by Daskalakis et al (2018), uses tests based on minimal pairwise correlations which are similar in spirit to some of the tests we consider. In a related work Gheissari et al (2017) demonstrated that sums of pairwise correlations concentrate for general Ising models.…”
Section: Connectivitymentioning
confidence: 99%